Saksi Mahkota dalam pembuktian pidana kasus Narkotika - Muhammad Syahputra; Muhammad Hatta; Zulfan Z (Fakultas Hukum Universitas Malikussaleh, 2021)
A crown witness is a witness who comes or is taken from one of the suspects or other defendants who jointly committed a criminal act, and in which case the witness is given a crown. The crown given to a witness with the status of a defendant is in the form of negating the prosecution of his case or the imposition of a very light charge if the case is submitted to court or is forgiven for wrongdoing. The formulation of the problem in this research is the strength of the testimony of the crown witness in proving narcotics trafficking and the existence of human rights if he is placed as the crown witness in proving the narcotics trafficking. This type of research is an empirical juridical research, namely an integrative and conceptual method of analysis to identify, process and analyze documents to understand the meaning, significance, and relevance that produces descriptive data in the form of written or spoken words from the people or observed behavior. . The results showed that the testimony of the crown witness was considered strong and as strong as the testimony of other witnesses because he was also under oath. The strength of the testimony of the crown witness in proving the narcotics trade in his position as the crown witness has not been regulated separately in the existing law. Crown witness itself is a term that can be interpreted as a defendant who has the status of being a witness in the case of another defendant who has both committed a criminal act, namely in the event that the case files are separated (splitsing) on the separation of the case files during examination based on Article 141 of the Criminal Procedure Code. Human rights are very much considered in the judicial process when the crown witnesses give information such as the absence of intervention that makes the crown witnesses depressed. The existence of human rights when placed as a crown witness in proving narcotics trafficking, where the crown witness is presented before the court because of the splitsing mechanism regulated in Article 142 of the Criminal Procedure Code (KUHAP). By splitting the case files into several stand-alone cases, between one defendant and another defendant, each of them can be used as a mutual witness. Meanwhile, if they are combined in one file and in a trial examination, they cannot be used as mutual witnesses between one another. It is recommended to the Government, especially the legislators, that if indeed this crown witness is an important tool to reveal a legal act, then it should make legislation that specifically regulates the existence of Crown Witness.